Drivers of Change: A Multiple-Case Study on the Process of Institutionalization of Corporate Responsibility Among Three Multinational Companies - Richter, Ulf Henning (2011)
In this multiple-case study, I analyze the perceived importance of seven categories of institutional entrepreneurs (DiMaggio, Institutional patterns and organizations, Ballinger, Cambridge, MA, 1988) for the corporate social responsibility discourse of three multinational companies. With this study, I aim to significantly advance the empirical analysis of the CSR discourse for a better understanding of facts and fiction in the process of institutionalization of CSR in MNCs. I conducted 42 semi-structured face-to-face and phone interviews in two rounds with 30 corporate managers from three multinational companies. The data has been analyzed using qualitative (multiple coding) and quantitative (ANOVA, χ2 analysis) techniques. The findings indicate that one company is driven by civil society’s influence on consumer’s perception, the second company by direct attacks by civil society, agenda setting organizations and legislators, and the third by the pressure of large customers and legislators. The results suggest that the coping behaviors of MNCs at both extremes of the spectrum of perceived responsible behavior aim at (1) improving the business case for CSR and (2) increasing legitimacy in society, resulting in converging CSR perceptions, and fostering an institutionalization of CSR.
Keywords: case study research; Legitimacy; institutional entrepreneurs; Corporate Social Responsibility